Portable Thermoelectric Cooler Box Performance with Variation of Input Power and Cooling Load - Afdhal Kurniawan Mainil; Azridjal Aziz; M Akmal (Graduate Program of Syiah Kuala University, 2018)
The thermoelectric module is a device that works by using the Peltier effect when electrical power supplied on it. In this study, the thermoelectric module is applied as thermoelectric cooler (TEC) using air cooling heat sink where cooling box capacity is 22 L. This paper experimentally investigates the thermal performance of thermoelectric cooler with a variation on input power and cooling load. The investigation has been conducted by three variations on input power (50.5W, 72.72W and 113.64W) and by two variations of the cooling load using mineral water (1440 mL and 2880 mL) with input power 113.64W. The box temperature achieved at input power 50.5W, 72.72W and 113.64W are 19.98oC, 19.77oC and 18.52oC, respectively. While at the cooling load of 1440 mL and 2880 mL, the temperature achieved in the box are 22.45oC and 23.32oC, respectively. The test results showed that in variation on the input power from low to high, the temperature in box becomes lower on high input power and causes the lower of COP, this is because more energy could be absorbed on high input power. In the cooling load variation, the greater the cooling load given in cooling box, then the longer the box temperature stability can be achieved because of more energy needed for decreasing the temperature of cooling box.